PENGEMBANGAN MEDIA INFOGRAFIS PADA MATERI MASUKNYA AGAMA DAN KEBUDAYAAN HINDU-BUDDHA DI NUSANTARA KELAS XI SMA NEGERI 9 KOTA - Octavianti, Neken; Azmi, Ulul (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2023)
This research begin from problems at SMA Negeri 9 Jambi City, namely the presence of studentswho did not understand the material, the lack of use of learning media during the learning processso that in learning the atmosphere became monotonous and boring. This study aims to find out thesteps for making infographic media and knowing the feasibility of infographic media. Thedevelopment model used is ADDIE which has five stages, namely analysis, design, development,implementation, evaluation. The developed media is then validated by media experts and materialexperts. In field trials, three stages of research were carried out, namely individual trials thatobtained 80% results with the "Good" category, small group trials obtained 84% results with the"Good" category and large group trials obtained 91% results with the "Very Good" category. So, itcan be concluded that Infographic media is "feasible" to use for students.